Technical Challenges of Tower Sharing in Multi-Operator Mobile Communication Environments - Koudjo Mawuefam Koumadi; Raymond Folley; Kester Quist-Aphetsi; Amevi Acakpovi (Institute of Advanced Engineering and Science, 2013)
The traditional mobile communications business model was based on full ownership of network infrastructure. However, network infrastructure sharing has been a trend among mobile network operators. Sharing traditional mobile network infrastructure which were not designed originally for sharing has become prevalent in the face of stiff competition, regulatory requirement and declining revenues. This, despite the reduction in capital expenditure for operators, brings technical challenges with regards to network planning, optimization and expansion in multi-operator shared environments. This paper briefly introduces models of passive infrastructure sharing and their advantages, and investigates the technical challenges which are inherent to communications tower sharing. The effects of non-optimal antenna height on coverage and signal quality, as well as those of tower loading constraints on transmission link quality are investigated among others. Simulation results and on-site measurements confirm these challenges, which may increase the operation expenditure of mobile networks.Our findings challenge the current perception in both academia and industry that passive infrastructure sharing can only produce positive effects, and therefore call for further investigations on the financial benefits of infrastructure sharing.DOI: http://dx.doi.org/10.11591/ij-ict.v2i3.4553